Association Between Lipoprotein(a) and Risk Factors of Atherosclerosis in Russian Population (Data of Observational ESSE-RF study) - S. A. Shalnova; M. V. Ezhov; V. A. Metelskaya; S. E. Evstifeeva; V. I. Tarasov; G. A. Muromtseva; Yu. A. Balanova; A. E. Imaeva; A. V. Kapustina; A. A. Shabunova; O. A. Belova; I. A. Trubacheva; et al. (Столичная издательская компания, 2019)
Experimental and clinical data indicate a significant contribution of lipoprotein(a) (Lp[a]) to the atherogenesis. However, the pathophysiological mechanisms of this relationship are not fully understood.Aim. To investigate the distribution of Lp(a) in the population of the regions participating in the Study "Epidemiology of Cardiovascular Diseases in the Regions of the Russian Federation" (ESSE-RF) and to evaluate its associations with cardiovascular risk factors.Material and methods. Representative samples of the male and female population of 7 regions of the Russian Federation, aged from 25 to 64 years, enrolled in the multi-center cross-sectional epidemiological study were analyzed. A total of 10332 people were examined, of whom 3732 were men (36.0%) and 6600 were women (64.0%), the average age was equal in both sexes.Results. The mean value of Lp(a) reached 22.4 mg/dl (standard deviation 21.3 mg/dl) and significantly differed from the median (11.1 mg/dl; interquartile range from 3.9 to 20.2 mg/dl), forming the right-skewed distribution in both male and female population. Lp(a) levels were statistically significantly correlated with the level of low-density lipoproteins cholesterol (LDL-C), ароВ/аpoAI and total cholesterol. Notably, the odds ratios were growing by quintiles, and increased along with increasing lipid values (p<0.0001). Lp(a) levels were also positively associated with high-sensitivity C-reactive protein (hs-CRP) and negatively correlated with blood concentration of glucose and triglycerides (TG). There were no associations with body mass index, waist circumference and smoking status.Conclusion. According to the ESSE-RF data, there are significant positive associations of Lp(a) with the LDL-C level, the ароВ/аpoAI ratio, total cholesterol, and hs-CRP. Negative associations are established with glucose and TG levels. The future studies should be planned with the notion of the Lp(a)'s right-skewed distribution type.